2016
DOI: 10.1007/s00167-016-4278-8
|View full text |Cite
|
Sign up to set email alerts
|

Changes in hindfoot alignment after total knee arthroplasty in knee osteoarthritic patients with varus deformity

Abstract: Prospective cohort study, Level II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
62
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(64 citation statements)
references
References 29 publications
2
62
0
Order By: Relevance
“…12 However, the evaluation of ankle joints after TKA has been examined only after MATKA. 19,22 Our results indicate that both MATKA and KATKA decrease the ankle joint compensatory change of alignment as reported in previous studies. Adding to what is known about decreased compensation, the present study indicates that KATKA restores ankle joint alignment closer to that of a control group compared with MATKA.…”
Section: Discussionsupporting
confidence: 89%
“…12 However, the evaluation of ankle joints after TKA has been examined only after MATKA. 19,22 Our results indicate that both MATKA and KATKA decrease the ankle joint compensatory change of alignment as reported in previous studies. Adding to what is known about decreased compensation, the present study indicates that KATKA restores ankle joint alignment closer to that of a control group compared with MATKA.…”
Section: Discussionsupporting
confidence: 89%
“…In patients with osteoarthritis, the varus alignment in the knee joint is associated with the valgus alignment in the rare foot and the valgus alignment in the knee joint is associated with the varus alignment in the rare foot (16,17). The deformity in the rear foot has been reported to be improved following TKA surgery in some studies (9,10,16,18). However, there are very few studies evaluating the changes occurring in the pressure and strength of the sole following TKA (19).…”
Section: Discussionmentioning
confidence: 99%
“…However, there are very few studies evaluating the changes occurring in the pressure and strength of the sole following TKA (19). It is reported in the literature that the knee arthroplasty surgeons are concerned that the presence of a noteworthy foot or ankle joint deformity might result in an abnormal load on the knee prosthesis and this in turn may cause early mechanical problems in the prosthesis (10). In a study by Voronov et al (20), a minimal change was found in the load on the foot following correction of the knee deformity by TKA and this condition was reported as the compliance ability of the subtalar joint complex to the load changes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 9 In addition, KOA individuals with varus alignment also demonstrated changes in foot kinematics, such as greater rearfoot valgus. 10 All these findings are indicative of decreased foot mobility 7 and can be attributed to a reduction in the compensatory capacity of the foot-ankle joint complex in response to varus alignment. 8 11 Thus, although still inconclusive, there is some evidence on the mechanisms by which kinematic changes in the feet influence pain and knee cartilage degradation.…”
Section: Introductionmentioning
confidence: 99%